2021
DOI: 10.1111/exd.14291
|View full text |Cite
|
Sign up to set email alerts
|

Mohs micrographic surgery in dermatofibrosarcoma protuberans: Rate and risk factors for recurrence in a prospective cohort study from the Spanish Registry of Mohs Surgery (REGESMOHS) and review of the literature

Abstract: Characterization of patients, surgery procedures and the risk factors for dermatofibrosarcoma protuberans (DFSP) recurrences is poorly defined. In this study, we aimed to describe the demographics, tumor characteristics and interventions of DFSP treated with Mohs micrographic surgery (MSS) to determine the rate and risk factors for recurrence. Data were collected from REGESMOHS, a nationwide prospective cohort study of patients treated with MMS in Spain. From July 2013 to February 2020, 163 patients with DFSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Over several months to many years, the early lesions slowly enlarge to form protuberant, indurated, reddish-blue to violaceous nodules. DFSPs range in size from 0.5 cm to > 10 cm and typically present on the trunk (40-50%), followed by proximal extremities (30-40%) and head and neck (10-15%) [2][3][4]6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over several months to many years, the early lesions slowly enlarge to form protuberant, indurated, reddish-blue to violaceous nodules. DFSPs range in size from 0.5 cm to > 10 cm and typically present on the trunk (40-50%), followed by proximal extremities (30-40%) and head and neck (10-15%) [2][3][4]6].…”
Section: Discussionmentioning
confidence: 99%
“…A dermoscopy is a valuable tool in tumor recognition and findings may prompt neoplasm diagnosis [5]. Although DFSP has a relatively good prognosis, it has a high propensity for recurrence and a rare potential for distant metastasis [2][3][4]. Standard treatment for DFSP involves complete surgical resection by either wide local excision (WLE) with margins or Mohs micrographic surgery (MMS) [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some benefits to slow‐Mohs, it is more expensive, time‐consuming, and may require patients to return for multiple surgeries, all of which limit the practicality of widespread use of this technique. Additionally, a recent analysis of patients with DFSP, who were included in the REGESMOHS (Spanish Registry of Mohs Surgery) trial from Spain, showed no difference in local recurrence between tumors evaluated by frozen section and those analyzed via paraffin section 42 . Table 2 summarizes selected series of MMS.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Additionally, a recent analysis of patients with DFSP, who were included in the REGESMOHS (Spanish Registry of Mohs Surgery) trial from Spain, showed no difference in local recurrence between tumors evaluated by frozen section and those analyzed via paraffin section. 42 Table 2 summarizes selected series of MMS.…”
Section: Mms and Slow Mohsmentioning
confidence: 99%
“…Medical records retrospect showing the 2 of 4 recurrence cases in this study owing to the positive margin while other 2 recurrence cases relapsed in 6 years later after rst surgery. According to the previous studies, Mohs micrographic surgery (MSS) associated with low recurrence rate of DFSP than WLE(15,20). Matthew T Houdek et al(21)indicated no statistical signi cance in oncologic outcomes comparing MMS with WLE in head and neck sites.…”
mentioning
confidence: 99%